Avoiding online censorship through ‘fatty’ memes: How Chinese social media users talk about North Korea - Zhang, Bingbing; Gearhart, Sherice; Perlmutter, David D (Global media and communication, 2022)
Memes are humorous images, often featuring captions with superimposed text, that are shared online. To avoid censorship, Chinese netizens strategically use memes to discuss political issues. This study content analyses memes that feature an image or likeness of North Korean leader Kim Jong-un posted by Chinese social media users on the Weibo platform. Results highlight how politically astute, tech-savvy publics can express political opinions and dissent in humorous ways, even in a high censorship online environment.